Vector Control of a Modular Multilevel Matrix Converter for Variable-Speed Drive Applications - Rojas-Lobos, F; Diaz-Diaz, M; Ibaceta-Valenzuela, E; Duran-Sepulveda, A (Institute of Electrical and Electronics Engineers Inc., 2019)
The Modular Multilevel Matrix Converter $(M^{3}C)$ has been proposed as an appropriate alternative for high-power drive systems due to characteristics for medium-voltage operation and power quality. Nevertheless, the control of $M^{3}C$ is complicated, especially in variable-speed applications, because large voltage oscillations can be produced in the floating capacitors. Therefore, this paper presents a vector control system that allows decoupled regulation of the floating capacitors of the $M^{3}C$, whereas Field Oriented Control (FOC) is applied to regulate an induction machine. The proposed control strategy considers an enhanced start-up of the machine for different load conditions. © 2019 IEEE.